Media Morality and Visual Icons in the Age of Social Media: Alan Kurdi and the Emergence of an Impromptu Public of Moral Spectatorship - Mortensen, Mette; Trenz, Hans-Jörg (Javnost-The Public, 2016)
New and social media are increasingly used to raise issues of global justice. Images and texts representing distant suffering in an emotionally charged way involve users of social media in debates about ethical standards and moral responsibility. This raises the question of how social media users react to such evidence about instances of distant suffering. How and under which conditions are users’ involvement in discourses of global justice enhancing new practices of civic engagement and redefining the boundaries of solidarity? Our point of departure is the so-called “refugee crisis” in Europe in fall 2015, which raised questions of distant spectatorship and moral responses with renewed urgency and immediacy. We consider the conditions of collective reception and interpretation of visual icons of human suffering, which became viral through social media in this period. We first situate social media reception in the framework for the analysis of moral spectatorship. We secondly explore the link between iconic images and the emergence of so-called impromptu publics of moral spectatorship. As an empirical case, we refer to the performance of reddit discussion groups in confronting the salient images of Alan Kurdi, the drowned boy from Syria found at the beach in Turkey in September 2015.